Test-Taking Motivation in Education Students: Task Battery Order Affected Within-Test-Taker Effort and Importance - Wolgast, Anett; Schmidt, Nico; Ranger, Jochen (Frontiers in Psychology, 2020)
Different types of tasks exist, including tasks for research purposes or exams assessing knowledge. According to expectation-value theory, tests are related to different levels of effort and importance within a test taker. Test-taking effort and importance in students decreased over the course of high-stakes tests or low-stakes-tests in research on test-taking motivation. However, whether test-order changes affect effort, importance, and response processes of education students have seldomly been experimentally examined. We aimed to examine changes in effort and importance resulting from variations in test battery order and their relations to response processes. We employed an experimental design assessing N = 320 education students’ test-taking effort and importance three times as well as their performance on cognitive ability tasks and a mock exam. Further relevant covariates were assessed once such as expectancies, test anxiety, and concentration. We randomly varied the order of the cognitive ability test and mock exam. The assumption of intraindividual changes in education students’ effort and importance over the course of test taking was tested by one latent growth curve that separated data for each condition. In contrast to previous studies, responses and test response times were included in diffusion models for examining education students’ response processes within the test-taking context. The results indicated intraindividual changes in education students’ effort or importance depending on test order but similar mock-exam response processes. In particular effort did not decrease, when the cognitive ability test came first and the mock exam subsequently but significantly decreased, when the mock exam came first and the cognitive ability test subsequently. Diffusion modeling suggested differences in response processes (separation boundaries and estimated latent trait) on cognitive ability tasks suggesting higher motivational levels when the cognitive ability test came first than vice versa. The response processes on the mock exam tasks did not relate to condition.